The Use Of Microsatellite Markers For Parentage Analysis In The Pacific Cupped Oyster, Crassostrea Gigas (Thunberg) ... - Boudry, P.; Collet, B.; Kotoulas, G.; Magoulas, A.; Hervouet, V.; Bonhomme, F.; Gérard, A. (ASC 1998 - K, 2024)
No abstracts are to be cited without prior reference to the author.Highly polymorphic genetic markers can be useful tools for the analysis of parental contributions. The present paper reports 3 experiments using microsatellite markers to analyse parental contributions in controlled in vitro factorial crosses of the cupped oyster Crassostrea gigas. Parentage analysis was eased by the large polymorphism observed at the 3 loci studied. In a cross between 20 males and 20 females, a quarter of the progeny could be assigned to a given parent using a single microsatellite locus showing 28 alleles. In 3 crosses between 5 males and females, all the progeny could be assigned to a family by using 3 loci. In all cases, the combined genotyping at 2 loci allowed parentage to be determined. unambiguously. Despite the balanced gametic contribution of each parent before fertilisation, unbalanced parental contributions are observed in the progeny, both at larval and juvenile stages. Evidence of gametic and zygotic competition ...